At the crossroads of international human rights law and international investment law: reflection on the right to development in the exercise of expropriation - Kim, Young Jae (My University, 2021)
Given the current legitimacy crisis of international law, particularly the international law of investment owing to fragmentation and the negative impact of unfettered economic development on the environment and human rights, competing claims between North and South, sovereign states and multinational corporations, and sovereign states and their nationals over development and its benefits must be effectively and legitimately reconciled before any strategy to promote development can be implemented. In this respect, the human right to sustainable development, which this thesis introduced, provides a framework in which the potential competing claims of economic value and human rights value can be reconciled. This thesis considers the interplay of international development law, international human rights law and international investment law, by reference to the evolution of a right to sustainable development. In particular, it focuses on how the international investment law regime has evolved to incorporate human rights and sustainable development, by examining expropriation as a case study. The thesis traces the concept of development as it underlines international development law, and shows how it has moved from ‘orthodox economic development’ to ‘modern human development’ by means of the evolution of the human right to sustainable development. It proceeds to contemplate the content of this human right to sustainable development, with a view to demonstrating its relevance to international investment law. Thereafter, it shows how international investment law has evolved over time, from being narrowly focused on upholding foreign investors’ interests and rights, to taking into account international human rights and the human right to sustainable development. As a concrete example of this shift in international investment law, the thesis then conducts a case study of expropriation, which illustrates the increased interaction between the three clusters of international law. In particular, the protection of foreign investors’ rights and host states’ rights to regulate foreign investment for the purpose of ensuring international human rights and sustainable development are explored through leading cases in international investment tribunals. In conclusion, it is argued that the legitimacy of the international investment law regime can be enhanced through continuing efforts of the international community to harmonise the three clusters of international law within the human right to sustainable development .
A thesis submitted to the in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2021
Keywords: UCTD; International Human Rights Law; International Investment Law; Right to Development; SDG-10: Reduced inequalities